Calcium-Sensing Receptor Gene Polymorphisms (CASRV1 and CASRV2) and the Physical Activity Level of Men in Lower Silesia, Poland - Zagrodna, Aleksandra; Ksia̧żek, Anna; Słowińska-Lisowska, Małgorzata; Łaczmański, Łukasz (Frontiers in Genetics, 2020)
Calcium-sensing receptors (CASR) are a dimeric family of C-class G-protein-coupled receptors that play a crucial role in bone and mineral metabolism by regulating parathyroid hormone (PTH) secretion, skeletal development, and urinary Ca2+ excretion. Genetic factors mainly impact bone mineral density (BMD). However, many variable factors may affect bone health, including physical activity. The aim of our study was to investigate the potential associations between calcium-sensing receptor gene polymorphisms (CASRV1 and CASRV2) and the level of physical activity in adult males from Lower Silesia, a region in the south of Poland. A total of 428 adult male inhabitants of Lower Silesia were included in the study. Their physical activity was evaluated using the International Physical Activity Questionnaire. The CASRV1 (rs 1801725, G>T, A986S) and CASRV2 (rs 761486, T>G, non-coding region) polymorphisms were determined using polymerase chain reaction (PCR) and mini-sequencing. The polymorphisms were identified with GeneScan software ver. 3.1.2. We did not observe any statistically significant differences between the total energy expenditure (total MET) and the CASRV1 and CASRV2 polymorphisms. We did not find any association between the level of physical activity and the frequency of genotypes at the polymorphic locus of the calcium-sensing receptor genes CASRV1 and CASRV2. We found that the number of hours the subjects spent in a sitting position was unrelated to the genotypes at the polymorphic locus of the calcium-sensing receptor gene CASRV1. Based on our studies, we concluded that there were no associations between CASR and physical activity in the men inhabiting Lower Silesia in Poland. Our results do not suggest any influence of the assessed genetic factors in the population variability of the level of physical activity of adults.